Molecularly Engineered Nanobodies for Tunable Pharmacokinetics and Drug Delivery - Glassman, Patrick M. (Bioconjug Chem, 2020)
The use of single-domain antibody fragments, or nanobodies, has gained popularity in recent years as an alternative to traditional monoclonal antibody-based approaches. Relatively little is known, however, about the utility of nanobodies as targeting agents for delivery of therapeutic cargoes, particularly to vascular epitopes or in the setting of acute inflammatory conditions. We used a nanobody (VCAMelid) directed against mouse vascular cell adhesion molecule 1 (VCAM-1) and techniques for site-specific radiolabeling and bioconjugation to measure targeting to sites of constitutive and inducible antigen expression and investigate the impact of various characteristics (affinity, valence, circulation time) on nanobody biodistribution and pharmacokinetics. Engineering of VCAMelid for bivalent binding (BiVCAMelid) increased affinity by an order of magnitude and provided 2.8- and 3.6-fold enhancements in splenic and brain targeting in naive mice, with a further 2.6-fold increase in brain uptake in the setting of focal CNS inflammation. In contrast, introduction of an albumin-binding arm (VCAM/ALB8) did not affect binding affinity, but its prolonged circulation time resulted in 3.5-fold and 17.4-fold increases in splenic and brain uptake at 20 min post-dose and remarkable 40-, 25-, and 15-fold enhancements in overall exposure of blood, spleen, and brain, respectively, relative to both VCAMelid and BiVCAMelid. Both therapeutic protein (superoxide dismutase, SOD-1) and nanocarrier (liposome) delivery were enhanced by conjugation to VCAM-1 targeted nanobodies. The bispecific VCAM/ALB8 maintained its superiority over VCAMelid in enhancing both circulation time and organ targeting of SOD-1, but its advantages were largely blunted by conjugation to liposomes.